Penerapan Metode Additive Ratio Assesment (ARAS) Pada Sistem Pemilihan Tempat Kursus Bahasa Inggris Online - Hari Setiyani (Jurnal Sistem Komputer dan Informatika (JSON), 2022)
The selection of the right place for the online English course is certainly expected to produce output that is in line with expectations. For this reason, a solution is needed to help make decisions on choosing the right place for online English courses. A system that can assist in making decisions and can provide recommendations for the right choice is a decision support system (DSS). In the implementation of DSS, appropriate methods or models are also needed according to the cases discussed. One method that can be used is the Additive Ratio Assessment (ARAS) method. The ARAS method is a multi-criteria decision-making method based on the concept of classification using the utility level by comparing the overall index value of each alternative with the overall optimal alternative index value. The system created has features or functions that are in accordance with the needs of using the ARAS method in calculating to perform alternative rankings. Based on the case studies conducted, ARAS was able to find the best alternative from several alternatives with Lister results of 0.459, Engoo of 0.635, Golden English of 0.702, English Academy of 1. The system was made using the XP methodology, with features including being able to manage criteria values, alternatives and count to display the ranking of the best alternatives. In terms of functionality, the system that has been made has met expectations or in other words 100% functions well, and produces calculations that are in accordance with manual calculations. This system can be implemented in a choice of online English courses quickly and precisely.